(untitled) (Third Sector Social Economic Review, 2022)
The main purpose of this study is to investigate the long-run relationship between agricultural loans and agricultural growth using quarterly data for the period 2005:1-2021:4. For this purpose, Autoregressive Distributed Lag (ARDL) bounds testing approach was used to investigate the existence of cointegration relationship between the variables. In the study, the agricultural gross domestic product represents the agricultural growth variable. On the other hand, agricultural loans provided by deposit banks, participation banks, development and investment banks were used to represent agricultural loans. The results of the analysis provided evidence that there is a long-run equilibrium relationship between agricultural growth and agricultural loans. In the long-run it has been determined that the increase in agricultural loans provided by deposit and participation banks have a positive effect on agricultural gross domestic product. In addition, error correction term coefficient was negative and statistically significant, which confirms the existence of a cointegration relationship between the variables.